Architects of Growth? : sub-national governments and industrialization in Asia ([s.l.] : Institute of Southeast Asian Studies, 2014)
Once acting as local representatives of the national government and content to let their larger counterparts do the'heavy lifting', state and provincial governments are increasingly expected to be stewards of their economies and deliver sustained growth rates for their citizens. Spurred on by increasing competition, not least from neighbouring territories, sub-national governments are increasingly formulating their own plans for economic development, taking out loans, investing in specialist facilities, and establishing marketing offices abroad.
Keywords: Economic development -- Political aspects -- Asia; Subnational governments -- Asia; Industrialization -- Asia; Electronic industries -- Asia